Die Beziehungen der südfranzösischen Ritterorden zu Juristen. Aufbau, - Krämer, Thomas (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2015)
In order to demonstrate that medieval military orders required assistance and advice from jurists, one does not need to refer to the Templar trial. Both Templars and Hospitallers needed individuals with legal expertise to support their interests and assert their legal claims. Until the fourteenth century, however, neither of the Orders made particular efforts to encourage their members to study canon and civil law. At the end of the twelfth century, Templars and Hospitallers began to establish special relationships with selected jurists in the cities of Southern France. Some urban commanderies had their own favourite jurists with whom they maintained, sometimes long-lasting, connections. These more or less unexceptional relations provided the basis for the establishment of wider networks of contact. Unfortunately, these interpersonal relationships were often quite informal which is why they can be hard to verify. However, a glimpse illustrating the importance and functioning of such networks is provided by the internal conflict within the Order of Saint John when it was divided between two rivalling masters: Foulque of Villaret and Maurice of Pagnac. Foulque of Villaret had good relations with the network associated with the papal curia in Avignon and had excellent contacts with cardinals as well as the Hospitaller elite of Southern France which played important role in his success over Maurice. The Templars, also made great efforts to establish networks of political influence providing privileged access to decision makers and information as well as to patronage. Nevertheless, these networking strategies had some disadvantages as they were costly and the military orders had to meet the expectations of other members of the network. Furthermore, networking did not secure certain success and the Order’s aspirations were not always fulfilled.